2005
DOI: 10.3122/jabfm.18.6.491
|View full text |Cite
|
Sign up to set email alerts
|

Risk Indices Associated with the Insulin Resistance Syndrome, Cardiovascular Disease, and Possible Protection with Yoga: A Systematic Review

Abstract: Objective: To conduct a systematic review of published literature regarding the effects of yoga, a promising mind-body therapy, on specific anthropometric and physiologic indices of cardiovascular disease (CVD) risk and on related clinical endpoints.Methods: We performed a literature search using 4 computerized English and Indian scientific databases. The search was restricted to original studies (1970 to 2004) evaluating the effects of yoga on CVD or indices of CVD risk associated with the insulin resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
270
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(279 citation statements)
references
References 122 publications
5
270
0
4
Order By: Relevance
“…Our results on chemical and biochemical parameters of metabolic change are consistent with other studies of the effect of yoga/meditation in MetS [12][13][14][15]. Khatri et al [12] reported in a randomized trial those 3 months yogic therapy resulted in a significant improvement in WC, SBP, DBP, fasting blood sugar, HbA1C, serum triglycerides and increase in HDL level.…”
Section: Discussionsupporting
confidence: 81%
“…Our results on chemical and biochemical parameters of metabolic change are consistent with other studies of the effect of yoga/meditation in MetS [12][13][14][15]. Khatri et al [12] reported in a randomized trial those 3 months yogic therapy resulted in a significant improvement in WC, SBP, DBP, fasting blood sugar, HbA1C, serum triglycerides and increase in HDL level.…”
Section: Discussionsupporting
confidence: 81%
“…Such interventions may also reduce symptoms by improving other indices of psychological and physical health. For instance, interventions involving physical activity, such as yoga, have been reported to reduce body fat and improve lipid profiles [86], as well as alleviate stress and low mood difficulties [87], which have, in turn, been associated with HFNS problem rating and severity [88]. Moreover, changes in other lifestyle factors (e.g.…”
Section: Possible Mechanisms Behind the Beneficial Effects Of Mind-bomentioning
confidence: 99%
“…7,18,24 Small clinical trials have shown benefits of yoga in patients with diabetes, 3,10 and a systematic review found that yoga improved metabolic risk factors. 9 Integrated yoga program has been shown to be helpful in reducing both post-chemotherapy nausea and anticipatory nausea and vomiting. This has been attributed to stress-reduction effects of yoga intervention.…”
Section: Yoga In Diseasementioning
confidence: 99%